The design thinking workbook : essential skills for creativity and business growth - Meadows, C. J.; Parikh, Charvi (Emerald Publishing Limited, 2022)
Design Thinking (DT) is popular in corporate innovation and start-ups alike for helping people to craft fresh, new solutions to today's challenges and develop underlying skills in high demand in tomorrow's economy: creativity, critical thinking, collaboration, insight, empathy, experimentation, and more. After years of research and practice in Design Thinking, CJ Meadows and Charvi Parikh have distilled their expertise into this definitive guide for making the most of this approach for business growth and problem-solving. In The Design Thinking Workbook, they guide you through the essential skills that underlie DT, and introduce the tools, techniques and processes that empower you to immediately apply DT to real-world situations. Their experiential, exercise-driven, and visual approach, awakens that part of the brain that draws, designs, and dreams. Anyone can be a Design Thinker. Businesspeople, policymakers, educators, social entrepreneurs, and others can use DT to solve problems, develop creativity, and design new solutions that make life easier and businesses more productive.